Novel propargylamine-based inhibitors of cholinesterases and monoamine oxidases: Synthesis, biological evaluation and docking study - Krátký, Martin; Vu, Quynh Anh; Štěpánková, Šárka; Maruca, Annalisa; Silva, Tiago Barros; Ambrož, Martin; Pflégr, Václav; Rocca, Roberta; Svrčková, Katarína; Alcaro, Stefano; Borges, Fernanda; Vinšová, Jarmila (Bioorganic chemistry, 2021)
A combination of several pharmacophores in one molecule has been successfully used for multi-target-directed ligands (MTDL) design. New propargylamine substituted derivatives combined with salicylic and cinnamic scaffolds were designed and synthesized as potential cholinesterases and monoamine oxidases (MAOs) inhibitors. They were evaluated invitro for inhibition of acetyl- (AChE) and butyrylcholinesterase (BuChE) using Ellman's method. All the compounds act as dual inhibitors. Most of the derivatives are stronger inhibitors of AChE, the best activity showed 5-bromo-N-(prop-2-yn-1-yl)salicylamide 1e (IC50 = 8.05 µM). Carbamates (4-bromo-2-[(prop-2-yn-1-yl)carbamoyl]phenyl ethyl(methyl)carbamate 2d and 2,4-dibromo-6-[(prop-2-yn-1-yl)carbamoyl]phenyl ethyl(methyl)carbamate 2e were selective and the most active for BuChE (25.10 and 26.09 µM). 4-Bromo-2-[(prop-2-yn-1-ylimino)methyl]phenol 4a was the most potent inhibitor of MAOs (IC50 of 3.95 and ≈10 µM for MAO-B and MAO-A, respectively) along with a balanced inhibition of both cholinesterases being a real MTDL. The mechanism of action was proposed, and binding modes of the hits were studied by molecular docking on human enzymes. Some of the derivatives also exhibited antioxidant properties. Insilico prediction of physicochemical parameters affirm that the molecules would be active after oral administration and able to reach brain tissue.
Keywords: hepatocyty; Monoamine Oxidase; propylaminy; Animals; Butyrylcholinesterase; butyrylcholinesterasa; Acetylcholinesterase; cholinesterasy; vztah mezi dávkou a účinkem léčiva; Antioxidants; Monoamine Oxidase Inhibitors; Rats, Wistar; Electrophorus; Molecular docking; simulace molekulového dockingu; Molecular Structure; Structure-Activity Relationship; lidé; Propylamines; Salicylic scaffold; Cholinesterases; Pargyline; Reactive Oxygen Species; Propargylamine; Monoamine oxidases; kultivované buňky; koně; monoaminoxidasa; Hepatocytes; Horses; Multitargeting ligands; pargylin; molekulární struktura; Cells, Cultured; Dose-Response Relationship, Drug; Male; inhibitory MAO; Enzyme inhibition; antioxidancia; reaktivní formy kyslíku; krysa rodu Rattus; vztahy mezi strukturou a aktivitou; zvířata; mužské pohlaví; cholinesterasové inhibitory; Cholinesterase Inhibitors; Rats; Molecular Docking Simulation; potkani Wistar; Humans